A hunter-gatherer's guide to the 21st century : evolution and the challenges of modern life - Heying, Heather; Weinstein, Bret (Portfolio/Penguin, 2021)
"For evolutionary biologists Heather Heying and Bret Weinstein, the cause of many modern woes is clear: the world is out of sync with humans' ancient brains and bodies. The authors cut through the disputes surrounding issues like sex, gender, diet, parenting, sleep, education, and more to outline a science-based worldview that will empower the reader to live a better, wiser life. They distill more than twenty years of research and first-hand accounts from the most biodiverse ecosystems on Earth into straightforward principles and guidance for confronting our culture of hyper-novelty"--